Organisation of Internal Controls and Financial Audits in the Public Sector Organisations - I. D. Demina; T. I. Krishtaleva (Учёт. Анализ. Аудит)
The purpose of the study is to analyze the problems associated with the way internal control and financial auditing are organised in budgetary and public sector organisations. The authors show that internal control, as a process of interrelated actions, ensures risk reduction in the course of achieving the desired results of the institution’s activities. The level of internal control is assessed during the activities carried out through the Federal Treasury and State (municipal) financial control and internal financial audit. The article describes the procedure for the development of the Regulations on internal Control; reflects the main distinguishing features of internal control and internal financial audit; a classification of violations (risks) of budget (accounting) accounting and reporting has been formed, as well as the procedure for drawing up an audit opinion. The study shows that in order to quickly find problem areas and make management decisions based on the identified factors, it is necessary to strengthen electronic SMART control (controlling), accounting for public finances, and, accordingly, conduct comprehensive scientific research in promising areas. Methods of systematisation, comparison, grouping of the information were used in the preparation and writing of the article. The practical significance lies in the application of conclusions and proposals made on the results of the study to improve internal control and audit, which will allow interested users to obtain more reliable and understandable information to make management decisions based on it. The article is intended for a wide range of readers, undergraduate and graduate students dealing with the problems of internal control.